THE REQUIREMENTS FOR THE CONTENT OF THE FUTURE BIOLOGY TEACHERS' ENVIRONMENTAL COMPETENCE IN THE EDUCATIONAL ENVIRONMENT OF WEST EUROPEAN COUNTRIES - Maryna Khrolenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article analyzes the general requirements for the content of future biology teachers' environmental competence in the West European educational environment. Based on the curricula of the University of Roehampton, the University of Leeds, the University of Glasgow (UK), the University of Namur, and the University of Liege (Belgium), the composition of the academic disciplines, their scope and content are characterized.